159k views
5 votes
Help!!

Marta is solving the equation S = 2πrh + 2πr2 for h. Which should be the result?

StartFraction S Over 2 pi r EndFraction equals h. – r = h
StartFraction S minus r Over 2 pi r EndFraction equals h. = h
S – S minus StartFraction r Over 2 pi EndFraction equals h. = h
S – S minus StartFraction 2 pi Over r EndFraction equals h. = h

2 Answers

5 votes

Answer:

(S-2πr^2)/ 2πr = h

Explanation:

S = 2πrh + 2πr^2

Subtract 2 pi r^2 from each side

S-2πr^2 = 2πrh + 2πr^2 -2πr^2

S-2πr^2 = 2πrh

Divide each side by 2 pi r

(S-2πr^2)/ 2πr = 2πrh/2πr

(S-2πr^2)/ 2πr = h

User Jason Stonebraker
by
5.1k points
3 votes

It is given that,

→ S = 2πrh + 2πr²

Now subtract 2πr² from the both sides,

→ S - 2πr² = 2πrh + 2πr² - 2πr²

→ S - 2πr² = 2πrh

Then divide both sides by 2πr,

→ (S-2πr²)/2πr = 2πrh/2πr

→ (S-2πr²)/2πr = h

Hence, (S-2πr²)/2πr = h is the result.

User Bigballs
by
4.8k points